2016
DOI: 10.1155/2016/2082946
|View full text |Cite
|
Sign up to set email alerts
|

α-Amylase andα-Glucosidase Inhibitory Saponins fromPolyscias fruticosaLeaves

Abstract: Three bisdesmosidic saponins 3-O-[β-D-glucopyranosyl-(1→4)-β-D-glucuronopyranosyl] oleanolic acid 28-O-β-D-glucopyranosyl ester (1), polyscioside D (2), and 3-O-{β-D-glucopyranosyl-(1→2)-[β-D-glucopyranosyl-(1→4)]-β-D-glucuronopyranosyl}oleanolic acid 28-O-β-D-glucopyranosyl-(1→2)-β-D-galactopyranosyl ester (3) were isolated from a methanol extract ofPolyscias fruticosa(L.) Harms leaves. Compound1was obtained as a main constituent and compound3was reported for the first time and named as polyscioside I. Saponi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 12 publications
0
21
0
Order By: Relevance
“…The yeast -glucosidase (G0660, Sigma-Aldrich) inhibition assay was performed using the substrate p-nitrophenyl--D-glucopyranoside according to the previously described method [12]. Briefly, the sample solution (2 L dissolved in DMSO) and 0.5 U/mL -glucosidase (40 L) were mixed in 120 L of 0.1 M phosphate buffer (pH 7.0).…”
Section: Assay For -Glucosidase Inhibitionmentioning
confidence: 99%
“…The yeast -glucosidase (G0660, Sigma-Aldrich) inhibition assay was performed using the substrate p-nitrophenyl--D-glucopyranoside according to the previously described method [12]. Briefly, the sample solution (2 L dissolved in DMSO) and 0.5 U/mL -glucosidase (40 L) were mixed in 120 L of 0.1 M phosphate buffer (pH 7.0).…”
Section: Assay For -Glucosidase Inhibitionmentioning
confidence: 99%
“…Especially important, given the high NCD (particularly diabetes) rates in the Pacific and northern Australia, are the anti-diabetes and anti-cardiovascular disease effects of most of the plants featured in the factsheets, demonstrated in scientific studies. Studies with evidence for this include the following: drumstick [ 36 , 37 , 38 , 50 , 60 ], amaranth [ 61 , 62 , 63 ], bele [ 64 , 65 , 66 ], chilli [ 67 , 68 , 69 ], purslane [ 70 , 71 , 72 ], kangkong [ 73 , 74 , 75 ], ofenga [ 76 , 77 , 78 ], hedge panax [ 79 , 80 ], chaya [ 39 , 40 ], pumpkin [ 81 , 82 ], and choko [ 83 , 84 ]. Their inclusion in the diet in sufficient quantity is likely to reduce the risk of diabetes and cardiovascular disease, not only by reducing glycemic load when they are included with high-carbohydrate meals, but also because of specific anti-diabetes effects.…”
Section: Resultsmentioning
confidence: 99%
“…The ethanol extract of N. fruticosus leaves also had AChE inhibitor activity with 22.8% ± 0.3% inhibition at 1,000 µg/ml. Three bisdesmosidic saponins were isolated from the methanol extract of N. fruticosus leaves (Hanh et al, 2016). Other studies in vivo reported that saponin compounds which were extracted from Fenugreek seeds (Trigonella foenum-graecum) increased the AChE inhibitor in Alzheimer's-induced rats (Khalil et al, 2016).…”
Section: Total Phenolic and Flavonoid Contentsmentioning
confidence: 99%